A Circle Problem!

Geometry Level 4

In the diagram above the red circle has radius R R and the blue circles have radius r r .

The upper blue circle is tangent to A P \overline{AP} and the red circle at T T and W W respectively and the lower blue circle is tangent to A P , P S \overline{AP}, \overline{PS} and A S \overline{AS} at V , U V, U and Q Q respectively.

If R r = a b \dfrac{R}{r} = \dfrac{a}{b} , where a a and b b are coprime positive integers respectively, find a + b a + b .


The answer is 17.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rocco Dalto
Feb 10, 2021

A Q = A V = 2 R x \overline{AQ} = \overline{AV} = 2R - x and A P S A T O \triangle{APS} \sim \triangle{ATO} \implies R 2 r r + x = 1 2 \dfrac{R - 2r}{r + x} = \dfrac{1}{2}

2 R 4 r = r + x x = 2 R 5 r P S = r + x = 2 ( R 2 r ) \implies 2R - 4r = r + x \implies x = 2R - 5r \implies \overline{PS} = r + x = 2(R - 2r) and

A P = A V + r = 6 r \overline{AP} = \overline{AV} + r = 6r

In A P S 4 R 2 = 4 ( R 2 4 r R + 4 r 2 ) + 36 r 2 16 r R = 52 r 2 \triangle{APS} \implies 4R^2 = 4(R^2 - 4rR + 4r^2) + 36r^2 \implies 16rR = 52r^2 \implies

R r = 13 4 = a b a + b = 17 \dfrac{R}{r} = \dfrac{13}{4} = \dfrac{a}{b} \implies a + b = \boxed{17} .

David Vreken
Feb 11, 2021

From segment O W OW , O T = O W T W = R 2 r OT = OW - TW = R - 2r .

Since A T O A P S \triangle ATO \sim \triangle APS by AA similarity, P S = O T A S A O = ( R 2 r ) 2 R R = 2 R 4 r PS = OT \cdot \frac{AS}{AO} = (R - 2r) \cdot \frac{2R}{R} = 2R - 4r .

By the Pythagorean Theorem on A P S \triangle APS , A P = A S 2 P S 2 = ( 2 R ) 2 ( 2 R 4 r ) 2 = 2 4 r R 4 r 2 AP = \sqrt{AS^2 - PS^2} = \sqrt{(2R)^2 - (2R - 4r)^2} = 2\sqrt{4rR - 4r^2} .

As an inradius of a right A P S \triangle APS , r = 1 2 ( P S + A P A S ) = 1 2 ( 2 R 4 r + 2 4 r R 4 r 2 2 R ) r = \frac{1}{2}(PS + AP - AS) = \frac{1}{2}(2R - 4r + 2\sqrt{4rR - 4r^2} - 2R) .

r = 1 2 ( 2 R 4 r + 2 4 r R 4 r 2 2 R ) r = \frac{1}{2}(2R - 4r + 2\sqrt{4rR - 4r^2} - 2R) rearranges to 3 r = 4 r R 4 r 2 3r = \sqrt{4rR - 4r^2} , then to 13 r 2 = 4 r R 13r^2 = 4rR , and finally to R r = 13 4 \frac{R}{r} = \frac{13}{4} .

Therefore, a = 13 a = 13 , b = 4 b = 4 , and a + b = 17 a + b = \boxed{17} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...